A Review of Pharmacology, Toxicity and Pharmacokinetics of 2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-Glucoside - Wang, Cheng; Dai, Shu; Gong, Lihong; Fu, Ke; Ma, Cheng; Liu, Yanfang; Zhou, Honglin; Li, Yunxia (Frontiers in Pharmacology, 2022)
Polygonum multiflorum Thunb. (He-shou-wu in Chinese), a Chinese botanical drug with a long history, is widely used to treat a variety of chronic diseases in clinic, and has been given the reputation of "rejuvenating and prolonging life" in many places. 2,3,4',5-tetrahydroxystilbene-2-O-β-D-glucoside (TSG, C20H22O9) is the main and unique active ingredient isolated from Polygonum multiflorum Thunb., which has extensive pharmacological activities. Modern pharmacological studies have confirmed that TSG exhibits significant activities in treating various diseases, including inflammatory diseases, neurodegenerative diseases, cardiovascular diseases, hepatic steatosis, osteoporosis, depression and diabetic nephropathy. Therefore, this review comprehensively summarizes the pharmacological and pharmacokinetic properties of TSG up to 2021 by searching the databases of Web of Science, PubMed, ScienceDirect and CNKI. According to the data, TSG shows remarkable anti-inflammation, antioxidation, neuroprotection, cardiovascular protection, hepatoprotection, anti-osteoporosis, enhancement of memory and anti-aging activities through regulating multiple molecular mechanisms, such as NF-κB, AMPK, PI3K-AKT, JNK, ROS-NO, Bcl-2/Bax/Caspase-3, ERK1/2, TGF-β/Smad, Nrf2, eNOS/NO and SIRT1. In addition, the toxicity and pharmacokinetics of TSG are also discussed in this review, which provided direction and basis for the further development and clinical application of TSG.